2021
DOI: 10.1039/d0sm01754j
|View full text |Cite
|
Sign up to set email alerts
|

Pressure tunable adhesion of rough elastomers

Abstract: The adhesion of rough surfaces comprised of dewetted thermoplastic asperities on an elastomer is controlled by changing the applied compressive load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Although we have initially performed this annealing in an inert atmosphere, our later experiments (vide infra) have demonstrated that the ambient atmosphere annealing is also possible, thanks to the good thermal stability and the robust chemical structure of 2EHO-TPA-CNPE. While heating above glass transition at relatively high temperatures (>200-250 °C) was typically required for the formation of dewetted structures in polymer thin films, [53,55,56] the dewetting dynamics are quite different in the case of nanoscopic molecular thin-films. The solid-state of molecular semiconductor thin-films, from the cumulative cohesive energetics perspective, are bound by relatively weak π-interactions and van der Waals forces, especially when compared with polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…Although we have initially performed this annealing in an inert atmosphere, our later experiments (vide infra) have demonstrated that the ambient atmosphere annealing is also possible, thanks to the good thermal stability and the robust chemical structure of 2EHO-TPA-CNPE. While heating above glass transition at relatively high temperatures (>200-250 °C) was typically required for the formation of dewetted structures in polymer thin films, [53,55,56] the dewetting dynamics are quite different in the case of nanoscopic molecular thin-films. The solid-state of molecular semiconductor thin-films, from the cumulative cohesive energetics perspective, are bound by relatively weak π-interactions and van der Waals forces, especially when compared with polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…Each film was then transferred onto the surface of a bulk elastomer, PDMS (Dow Sylgard 184) using a film transfer method detailed in the previous publication. [ 13 ] The bilayer polymer sample is thermally annealed at 160 °C (above the glass transition temperature of PS) for 24 h. The now mobile PS polymer chains dewet from the PDMS substrate to minimize surface area. The droplets arrange into a polygonal pattern that is characteristic of thin film dewetting and solidify upon quenching to leave stiff asperities on the substrate surface.…”
Section: Methodsmentioning
confidence: 99%
“…A scalable and universal strategy, which enables the modification of any adhesive surface for pressure‐tunable adhesion and easy release on a variety of substrate materials and geometries, has yet to be realized. Previously, [ 13 ] we presented a new and generalized approach to obtain a material with pressure‐tunable adhesion. This new pressure‐tunable adhesive (PTA) is a surface patterned material that utilizes polymer thin film dewetting.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic features in the surface morphologies of natural and artificial soft materials are known to effectuate morphology-driven DOI: 10.1002/mame.202200247 and stimuli-responsive functionality through switchable or tunable adhesion, wettability, and optical responses. [1][2][3][4][5] Easy and robust methods to prepare soft surface wrinkles with controlled structural features are required for customizing and optimizing the application of soft materials in various technological disciplines. Patterning thin polymer films in 3D morphologies is an active research area as these materials find applications in various areas such as stretchable electronics, functional skins, tunable optical devices, tunable surface wetting, adhesion, water collection, triboelectric nanogenerators (TENGs), and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%